Borrowers’ Dispute with Banks over the Use of Variable WIBOR Rate in PLN Mortgage Loans - Walitza, Andrzej (Acta Universitatis Lodziensis. Folia Oeconomica, 2025)
The article investigates the escalating legal conflicts between mortgage borrowers and financial institutions regarding the application of the variable WIBOR (Warsaw Interbank Offered Rate) reference rate in mortgage agreements. The variability in judicial decisions thus far has heightened the likelihood of an increased number of lawsuits. The research examines the legal, economic and regulatory foundations underpinning borrower claims, as well as the potential repercussions for the mortgage market in the event that WIBOR-based contracts are effectively contested. It delves into macroeconomic determinants such as the escalation of inflation and interest rates, along with the role of monetary policy communication in shaping borrower behaviour. Systemic challenges, including constraints within the mortgage market and efforts to reform the national benchmark, are also examined. The analysis assesses assertions that banks intentionally neglected to offer fixed rate options and investigates similarities with previous judgments regarding foreign currency mortgages. Employing case law analysis and statistical techniques, the article rigorously contrasts the arguments of borrowers with the defences of banks, ultimately upholding the validity of WIBOR within both national and EU legal frameworks. The results illuminate systemic deficiencies in mortgage regulation and emphasise the pressing need for reforms in practices related to variable-rate lending.